ANALYSIS THE FORMULA OF STRESS INTENSITY FACTORS FOR THE COMPACT TENSION SHEAR TEST - YUAN WeiJun; XIE YuJun; CHENG ZhiFei (Jixie qiangdu)
The Compact Tension Shear（ CTS） specimen proposed by Richard is a commonly test type used in mixed ModeI/II loading. The formula of stress intensity factors（ SIFs） for the CTS test has already given by relevant literature. Since the formula appeared in different forms in the subsequent research,it is very necessary to determine the correct formula of SIFs for the CTS test. By comparing the various formulas obtained by the literatures with the normalized SIFs‘ curve in Richard’s original articles,this paper identifies the correct formula of SIFs for the CTS test in Richard’s original articles. CTS specimens made from general-purpose Polystyrenes（ GPPS） under mixed Mode-I/II loading were investigated to verify the correctness of the formulas of SIFs provided in Richard’s original articles. Compared the SIFs calculated by using the formulas appeared in the literatures and the extended finite element method（ XFEM） by Abaqus. Finally,the formula of SIFs for CTS test can be determined.